ONE POT SYNTHESIS OF 3-(SUBSTITUTED PHENOXYMETHYL)-6-PHENYL/SUBSTITUTED PHENOXYMETHYL-1,2,4-TRIAZOLO[3,4-B][1,3,4] THIADIAZOLE DERIVATIVES AS ANTIMICROBIAL AGENTS - RAJESH D. HUNASHAL; D. SATYANARAYANA (International Journal of Pharma and Bio Sciences, 2012)
The reaction of thiocarbohydrazide with substituted phenoxy acetic acid to obtained 3-substituted-4-amino-5-mercapto-1,2,4-triazoles (1) by condensing compound 1 with aromatic carboxylic acid and substituted phenoxy acetic acids resulted the title compound triazolothiadiazoles 2a-j. The purity of the newly synthesized compounds was confirmed by TLC. Structures of all the newly synthesized compounds were confirmed by spectral data. All the newly synthesized compounds were screened for their in-vitro antimicrobial activity. Among the series the compounds 2e, 2f and 2b, 2c, 2f, 2d, 2i were exhibited equipotent antibacterial and antifungal activity at MIC of 1 µg/mL when compared with standard drugs respectively. From the results the compounds 2c, 2f, 2j were showed comparable antitubercular activity against M. tuberculosis H37Rv at MIC of 0.50 µg/mL, when compared with standard drug Rifampin and INH which showed MIC of 0.25 µg/mL.